Cardioprotective Chinese herbs and antiretroviral drug metabolism: a systematic review of in vitro evidence - Cheng, Wan-Jung; Jaworowski, Anthony; Trevillyan, Janine M.; Hearps, Anna C.; Xue, Charlie C.; Zhang, Anthony L. (Frontiers in Pharmacology, 2025)
IntroductionThere is considerable potential for using Chinese Herbal Medicine to manage inflammatory co-morbidities, including cardiovascular disease, in people with HIV. However, any use would require understanding herb–drug interactions with antiretroviral (ARV) drugs to ensure safety. We evaluate evidence for the effect of selected cardioprotective Chinese herbs on the activity of cytochrome P450 (CYP) enzymes that metabolise ARV drugs.MethodsWe conducted a comprehensive review of six Chinese herbs commonly found in Chinese herbal formulas for treating cardiovascular conditions. We examined the effects of their extracts and reference bioactive molecules on CYP expression and enzymatic activity. The review focused on evidence from in vitro laboratory studies. The included herbs were Dan Shen, Huang Qi, Bai Zhu, Dang Gui, Chuan Xiong, and Gan Cao. Study quality was assessed using the SciRAP 2.1 risk of bias tool, and results were grouped according to experimental methodology.Results426 articles were identified of which 24 met the inclusion criteria. Overall risk of bias was low. Dan Shen and Gan Cao were the most frequently studied herbs. The most common outcome reported was no significant effect on enzyme activity, occurring in 61% of assays for Dan Shen, 37% for Gan Cao, 47% for Dang Gui, and 67% for Huang Qi. Aqueous extracts, representing the most clinically relevant preparation, of Dan Shen had minimal impact on CYP activity, while those of Gan Cao indicated potential for enzyme inhibition. In contrast, aqueous extracts of the other herbs showed a tendency toward enzyme induction.DiscussionThese findings suggest that there is great potential for use of Chinese herbal medicine in managing inflammatory co-morbidities in people with HIV, but that careful consideration of herb-ARV drug interaction is warranted. While Dan Shen appears relatively safe to use in individuals receiving ARV therapy, caution is warranted for other herbs. We highlight the importance of clinically relevant extraction methods in herb–drug interaction studies. Since individual herbs may have opposing effects on ARV drug metabolism, studies conducted using whole formulae are critical.